RETRACTED: Role of Green Financing and Eco-Innovation for Energy Efficiency in Developed Countries: Contextual Evidence for Pre- and Post-COVID-19 Era - Wu, Hong; Fareed, Zeeshan; Wolanin, Elżbieta; Rozkrut, Dominik; Hajduk-Stelmachowicz, Marzena (Frontiers in Energy Research, 2022)
Following the environmental concerns such as global warming, climate change, and environmental degradation, scholars and policymakers discovered energy utilization as the key factor in these issues. Therefore, economies are paying more attention to green finance and eco-innovation to reduce energy usage and enhance energy efficiency. The prime objective of this study is to explore whether the mentioned variables exhibit any influence on the energy efficiency target achievement. In this sense, the current study explores the association of green finance and eco-innovation with energy intensity in the group of seven economies from 1990 to 2020. Using panel data approaches, this study employs diagnostic tests, that confirm the heterogeneous slopes and the existence of panel cross-section dependence. Also, the cointegration tests validate the existence of a long-run equilibrium relationship between the variables. Based on the asymmetric distribution of the data, this study employs the method of moments quantile regression. The empirical results reveal that green finance and eco-innovation significantly reduce energy intensity across the selected quantiles. Control variables such as urban growth and trade openness also adversely affect energy intensity. However, economic growth is to be the only significant factor that enhances energy intensity. The results are robust as validated by the panel quantile regression and the Granger panel heterogenous causality test. Based on the findings, this study recommends that green finance be promoted, as well as environmental-related technology innovation be encouraged, in order to achieve the goal of energy efficiency in developed economies. This study also provides additional policies appropriate for environmental recovery.